2022
DOI: 10.21037/atm-22-4222
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of intraoperative bleeding and blood transfusion in patients with recurrent retroperitoneal liposarcoma: a retrospective study

Abstract: Background: Surgery is the main treatment for recurrent retroperitoneal liposarcoma (RPLS). The aim of the present study was to explore the factors associated with blood loss during surgery for recurrent RPLS.Methods: This retrospective study included patients with first recurrence of RPLS who were treated at our hospital between January 2015 and December 2019. Factors associated with intraoperative blood loss were identified by univariate and multivariate logistic regression analyses. Receiver-operating chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The present study also indicated that the incidence of tumor recurrence was significantly lower in the well-differentiated group and the de-differentiated histological subtype was able to be used as an independent risk factor of LRFS for PRPLS cases. De-differentiated PRPLS frequently has an incomplete tumor capsule and irregular tumor shape, which makes the boundary between the tumor and normal tissue difficult to identify, thus prolonging the operation time, increasing intraoperative bleeding and hampering the completion of radical resection (10,19,23,24).…”
Section: Univariate Analysismentioning
confidence: 99%
“…The present study also indicated that the incidence of tumor recurrence was significantly lower in the well-differentiated group and the de-differentiated histological subtype was able to be used as an independent risk factor of LRFS for PRPLS cases. De-differentiated PRPLS frequently has an incomplete tumor capsule and irregular tumor shape, which makes the boundary between the tumor and normal tissue difficult to identify, thus prolonging the operation time, increasing intraoperative bleeding and hampering the completion of radical resection (10,19,23,24).…”
Section: Univariate Analysismentioning
confidence: 99%